The NADC30-like PRRSV activates the integrin αV subunit to facilitate its entry into Marc-145 cells - Chunlin Li; Jin Cui; Hui Zheng; Zhou Sha; Rong Wei; Rui Wu; Bo Ni (PLoS ONE, 2025)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a highly contagious virus that poses a significant threat to the global pig farming industry, resulting in substantial economic losses. However, owing to the high variability of PRRSV and unclear mechanisms of infection, there are currently no effective vaccines or drugs available for its prevention and control. Our previous report revealed that highly pathogenic PRRSV (HP-PRRSV) requires the FAK-PI3K-AKT signaling pathway to facilitate its entry into cells. In this study, we further investigated whether the integrin subunit was involved in the entry process of NADC30-like PRRSV. First, the integrin subunits in Marc-145 cells were characterized by RT-PCR, and 11 of these subunits were identified, nearly all of which interacted with the integrin α V and β1 subunits to form heterodimers. Western blot analysis revealed that the integrin α V subunit was highly expressed in Marc-145 cells, and blocking this subunit with a functional antibody or siRNA significantly attenuated NADC30-like PRRSV entry without affecting virus binding. Moreover, in Marc-145 cells, NADC30-like PRRSV could activate the FAK-PI3K-AKT signaling pathway through the integrin α V subunit. Blocking the α V subunit significantly inhibited signal transduction and virus entry, and treatment of cells with the PI3K activator greatly reversed this inhibitory effect. Furthermore, the α V subunit activator manganese could also enhance NADC30-like PRRSV entry and signal transduction. In conclusion, our results revealed that NADC30-like PRRSV could activate the integrin α V subunit and subsequently transduce signals to the FAK-PI3K-AKT signaling pathway to facilitate entry into Marc-145 cells.